The black hole mass vs bulge mass relationship in spiral galaxies - Marconi, A; Axon, D; Atkinson, J; Binney, J; Capetti, A; Carollo, M; Dressel, L; Ford, H; Gerssen, J; Hughes, M; Macchetto, D; Maciejewski, W; et al. (2000)
We describe an on-going HST program aimed at determining the relationship between the nuclear black hole mass and bulge mass in spiral galaxies. We have selected a volume limited sample of 54 nearby spiral galaxies for which we already have ground based emission line rotation curves, CCD surface photometry and radio maps. We are now obtaining HST/STIS longslit observations of each of the galaxies in the sample in order to determine the nuclear Halpha rotation curve at high (~0.1") spatial resolution. We will use these data to measure the unresolved dark mass concentration at the nucleus of each object. Here we show the first results from observations of objects in the sample.